1992
DOI: 10.1161/01.str.23.8.1111
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of endothelium-dependent relaxation in human basilar artery after subarachnoid hemorrhage.

Abstract: Background and Purpose: The goal of this study was to determine the alterations in vascular reactivity of human basilar artery after subarachnoid hemorrhage.Methods: Human basilar arteries were obtained from subjects who died within 1 day after subarachnoid hemorrhage and control subjects who died from causes other than brain involvement. Basilar artery strips were suspended for isometric tension recording in Krebs-Ringer solution. Morphometric study was also carried out on paraffin-embedded sections stained w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(37 citation statements)
references
References 44 publications
1
35
0
1
Order By: Relevance
“…A number of studies suggest that nitric oxide (NO)-mediated vasodilation is impaired in large-diameter cerebral arteries in experimental models of SAH (5, 13). Similar findings have been reported in basilar arteries of SAH patients (23). However, the contribution of endothelial dysfunction to cerebral artery constriction is controversial, and others have reported that endothelium-dependent relaxation is unchanged after SAH (8,39).…”
Section: Discussionsupporting
confidence: 87%
“…A number of studies suggest that nitric oxide (NO)-mediated vasodilation is impaired in large-diameter cerebral arteries in experimental models of SAH (5, 13). Similar findings have been reported in basilar arteries of SAH patients (23). However, the contribution of endothelial dysfunction to cerebral artery constriction is controversial, and others have reported that endothelium-dependent relaxation is unchanged after SAH (8,39).…”
Section: Discussionsupporting
confidence: 87%
“…22 Alternatively, endothelial dysfunction may also impose an increased vulnerability for DCI in patients early after SAH. 22,23 Furthermore, the increased incidence of DCI after concomitant early perfusion impairment and increased subarachnoid blood clot (high-risk group) in our study may reflect an exacerbation of SAH-related endothelial dysfunction. 24 Finally, our results reflect recent studies on the dissociation of angiographic vasospasm and poor neurological outcome and support the assumption that cerebral infarction might reflect the ultimate end point of different, proischemic pathomechanisms (eg, microthromboembolism, microvascular spasm, cortical spreading ischemia, impaired autoregulation).…”
Section: Discussionmentioning
confidence: 70%
“…Similarly, dilation of basilar arteries in response to thrombin was reduced after subarachnoid hemorrhage, and that in response to vasopressin was abolished (27). Reduced dilation of arteries to stimulation by thrombin, bradykinin, and Ca2+ ionophore A23187 has been reported, whereas relaxation to SNP was not affected in basilar artery from human patients after subarachnoid hemorrhage (28). The mechanism(s) by which cerebral vessels lose the ability to dilate in response to selective vasoactive stimuli after exposure to blood is not well understood.…”
Section: Discussionmentioning
confidence: 76%